A Study of Spousal Domestic Violence in an Urban Slum of Mumbai - Shrivastava, Prateek S (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Gender-based violence is recognized as a major issue on international human rights agenda. Domestic violence and abuse can happen to anyone, yet the problem is often overlooked, excused, or denied. This is especially true when abuse is psychological, rather than physical. METHODS: A community-based cross-sectional study of 6 months duration was undertaken with the objective of studying the proportion and different forms of domestic violence, factors influencing it, and to study treatment-seeking behavior of these women. The study participants were married women in the age group 18–45 years residing in an urban slum area of Malwani, Mumbai. Using stratified random sampling, 274 subjects were selected. House to house visits were paid and they were interviewed face to face using a pretested semi-structured questionnaire after obtaining their informed consent. Rapport was established with the help of a Medical Social Worker. The questionnaire included information pertaining to the sociodemographic parameters and experience of domestic violence in the last 1 year and their treatment-seeking behavior for the same. Utmost care was taken to maintain privacy and confidentiality. Analysis was done using SPSS version 17. RESULTS: The proportion of domestic violence was 36.9%. The most common form of violence was verbal in 87 (86.1%) followed by physical in 64 (63.4%). CONCLUSION: A significant association was found between domestic violence and age, education, spousal alcoholism, and duration of marriage.